Analisis Risiko Bagi Negara Republik Indonesia Terhadap Keberlakuan Bilateral Investment Treaty Antara Indonesia dan Singapura - Michael Michael (LPPM Universitas Ekasakti Padang, 2023)
On March 9th, 2021, Government of Republic of Indonesia and Government of Republic of Singapore exchanged ratification instruments of Bilateral Investment Treaty (BIT) in order to validate the BIT. Other than to increase and protect investment the enactment of BIT Indonesia-Singapore also contains certain risks. One of them is the provision on national treatment in BIT Indonesia-Singapore which emphasizes the obligation of central and local governments to provide same treatment as for local investors. This is a risk for Indonesia with many local governments across 38 provinces. The provisions of BIT Indonesia-Singapore regarding expropriation have narrow and rigid terms of expropriation and the high compensation, so it will be risky if Government of Republic of Indonesia expropriates the investments from Singaporean foreign investor. BIT Indonesia-Singapore also regulates third party funding in events of dispute between the Government of the Republic of Indonesia and Singaporean foreign investors. Considering that the foreign investors can receive third party funding, this can be risky for Indonesian Government because an amicable settlement will be difficult to achieve due to third party interests and the claim value will be higher as the third party funding will be also included in there.